The fifth quarter - Dawson, Mike, 1975- (Dawson, Mike, 1975- Fifth quarter, 2021)
Lori Block and her best friend Sophia are dedicated to their Fourth-Grade basketball team, despite being relegated to the 5th quarter, an extra period before the real game starts, where the not-so-good kids play, and the points don't count. That doesn't matter to Lori though, because basketball is a place where working hard and getting better gives her hints of self-confidence. At school, she is awkward and unsure, and at home Lori's parents are consumed by her mother's bid for local government. With athletic promise and a dogged determination to keep improving, Lori pursues her passion while navigating awkward social dynamics, her own expectations and her first overnight away from home. Can she find her confidence in school, at home, and on the court?